Disability and discourse analysis : looking at the purple parade - Ong, Hannah Si Min (Nanyang Technological University, 2020)
The Purple Parade is a movement held in Singapore annually advocating for inclusion as well as the celebration of the abilities of the disabled. With a multitude of viewpoints regarding the event, from the government applauding such efforts, to some of the disabled themselves criticising the lack of direction of the organising committee, it would thus be interesting to look at the language use of the website of the event itself. Using Pauwels’ multimodal framework to analyse the Purple Parade website, this study aims to see if and how inclusion is being discussed on the site, and in whose interests do such notions of inclusion, if present, serve, as well as its implications. Findings suggest that inclusion is indeed being mentioned on the website, and in two main ways – firstly, by excluding the very people they are trying to include, the disabled, and secondly, by framing inclusion as a showcase. However, reasons have been outlined as to why such notions of inclusion are present on the website, which is that the important stakeholders are pragmatic in nature, and that there are real intentions in wanting to push for change for the disabled.